The impact of IT tools for the creation and implementation of marketing strategy: Wpływ narzędzi IT na kreowanie i realizowanie strategii marketingowej - Golik-Górecka, Grażyna (Management and Administration Journal, 2021)
The purpose of this article is to analyse the impact of key IT tools for the implementation of marketing strategies and logistics. This analysis is to identify the level of effectiveness of the strategy in companies in the context of the opportunities created by Business Intelligence systems used in various areas of business intelligence and decision support. Today, they are already treated as business standards conditioning the effective management of an enterprise. Information began to play a special role and efficient way of obtaining it -expanding resource data collected by the company. This gave rise to the development of marketing information systems that support decision-making at every level of the marketing operation of businesses and the implementation of their strategy. Thus, by using Business Intelligence and Business Performance Management system it improves the quality of decisions and the effectiveness of the integration of multiple processes presented in the form of dashboards and scorecards. It should therefore be considered in the context of the BPM model, which purpose is to obtain synthetic information presented in the form of a recommendation of the decision-making associated with the implemented strategy. The confirmation of the thesis of supporting marketing strategies through IT tools will be presented as a case study of a particular company.